The Peroxisomal-CoA Synthetase MoPcs60 Is Important for Fatty Acid Metabolism and Infectious Growth of the Rice Blast Fungus - Zhang, Ting; Li, Ya-Nan; Li, Xue; Gu, Wangliu; Moeketsi, Emily Kolojane; Zhou, Ruiwen; Zheng, Xiaobo; Zhang, Zhengguang; Zhang, Haifeng (Frontiers in Plant Science, 2022)
Fatty acid metabolism is important for the maintenance of fatty acid homeostasis. Free fatty acids, which are toxic in excess, are activated by esterification with coenzyme A (CoA), then subjected to β-oxidization. Fatty acid β-oxidation-related genes play critical roles in the development and virulence of several phytopathogens. In this study, we identified and characterized a peroxisomal-CoA synthetase in the rice blast fungus Magnaporthe oryzae, MoPCS60, which is a homolog of PCS60 in budding yeast. MoPCS60 was highly expressed during the conidial and early infectious stages, and was induced under oleate treatment. Targeted deletion of MoPCS60 resulted in a significant reduction in growth rate when oleate and olive oil were used as the sole carbon sources. Compared to the wild-type strain Guy11, the ∆Mopcs60 mutant exhibited fewer peroxisomes, more lipid droplets, and decreased pathogenicity. The distribution of MoPcs60 varied among developmental stages, and was mainly localized to peroxisomes in the hyphae, conidia, and appressoria when treated with oleate. Our results suggest that MoPcs60 is a key peroxisomal-CoA synthetase involved in fatty acid β-oxidation and pathogenicity in rice blast fungi.